Penguatan Kurikulum, Sistem Pendukung, dan Lingkungan Sosial Sekolah dalam Menumbuhkan Tradisi Toleransi dan Penghargaan Identitas Peserta Didik - Masfufah, Masfufah; Darmawan, Didit (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the understanding and commitment of educational stakeholders, namely teachers, school management, and the community, to implementing multicultural education as a response to the issue of intolerance. The research data sources come from national and international scientific journals, research articles, reference books, and relevant educational policy documents and publications published in the last two decades. Data collection techniques from relevant and credible literature, with data analysis techniques using content analysis methods to identify patterns, supporting factors, and challenges in the process of internalizing tolerance values, this study found that the main factors supporting the success of multicultural education are responsive curriculum updates, practice-based teacher training, the formation of inclusive teams, strengthening social networks, and the integration of digital media as a learning medium. Constructive collaboration between parties within the school environment, as well as family and community involvement, has proven vital to realizing the internalization of values of tolerance and respect for different identities among students. These findings underscore the importance of synergy across educational elements and the need for policies that are responsive and adaptive to global social and technological dynamics.